Evaluating the administrative performance of the deans of faculties and heads of physical education departments according to the requirement of total quality (decision making). (Journal of the College of Basic Education, 2022)
Chapter one: the research problemThe evaluation process is a delicate and sensitive process that cannot be dispensed with in any educational institution such as schools, institutes and universities. It requires the person who performs the evaluation to have high skill in management and administrative competence that enables him to adopt accurate standards in judging performance. It is done according to modern methods of evaluation if we want these directorates to achieve the objectives set for them.Through what has been presented on the subject, the researchers are convinced that there is a deficiency in the performance of the deans of faculties and heads of physical education departments in accordance with the requirements of total quality from the point of view of the teaching staff, and this is evident through the most important